استخدام الحبة السوداء وتأثيرها في مستوى هرمون الاريثروبوتين وانجاز لفعالية - خلف حيدر, علاء (دفـاتر المـــــــــــخبـر; No 19 (2018): مجلة دفاتر, 2018)
لقد استأثرت دراسة التكيفات الوظيفية لأجهزة الجسم واعضائه المختلفة اهتمام الباحثين على مدى السنوات الاخيرة لإيمانهم بان الرياضي يتمكن من الوصول الى درجة عالية من الاداء البدني من خلال الية منسقة في  سلسلة من العمليات المتكاملة لأجهزة الجسم المختلفة   الا ان  هناك اجهزة لا تقل اهمية في تحديد  مستوى الانجاز الرياضي ومنها الهورمونات المهمة والحيوية منها هرمون الاريثروبوتين لدوره الفعال في زيادة الكفاءة الوظيفية للدورة الدموية من خلال استخدام النباتات الطبية ومنها الحبة السوداء التي تزيد من نسبة هذا الهورمون بشكل طبيعي دون تأثير جانبي له من خلال البناء الصحيح لعمل الخلايا  وتعويض ما ينقص الجسم وسد الاحتياجات الاساسية للرياضي.  الكلمات المفتاحية: الحبة السوداء، هرمون الاريثروبوتين، 1500متر حرة        The study of functional adaptations of the body and its various organs has been of interest to the researchers over the last few years. They believe that the athlete is able to achieve a high degree of physical performance through a coordinated mechanism in a series of integrated processes of the various body systems. However, there are no less important devices in determining the level of athletic achievement Including the important and vital hormones, including the hormone of erythropoietin to the role of effective in increasing the functional efficiency of the blood circulation through the use of medicinal plants, including black bean, which increases the proportion of this hormone naturally without the side effect through the Build the correct cells to work and compensate for what the body lacks and the basic needs of the athlete key words  Black bean, erythropoietin hormone, 1500 m free